2018
DOI: 10.1113/jp275492
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking T‐wave alternans to spontaneous initiation of ventricular arrhythmias in rabbit models of long QT syndrome

Abstract: T-wave alternans (TWA) and irregular beat-to-beat T-wave variability or T-wave lability (TWL), the ECG manifestations of action potential duration (APD) alternans and variability, are precursors of ventricular arrhythmias in long QT syndromes. TWA and TWL in patients tend to occur at normal heart rates and are usually potentiated by bradycardia. Whether or how TWA and TWL at normal or slow heart rates are causally linked to arrhythmogenesis remains unknown. In the present study, we used computer simulations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 65 publications
5
48
0
Order By: Relevance
“…Since phase-2 EADs cannot propagate into PVCs in tissue [1922], this raises question on how are EADs linked to arrhythmias under LQTS and many other diseased conditions where Ca 2+ may not be overloaded. In recent studies [22, 64], we demonstrated how phase-2 EADs and tissue-scale dynamical instabilities interact to result in PVCs and arrhythmias under LQTS, linking mechanistically phase-2 EADs to arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since phase-2 EADs cannot propagate into PVCs in tissue [1922], this raises question on how are EADs linked to arrhythmias under LQTS and many other diseased conditions where Ca 2+ may not be overloaded. In recent studies [22, 64], we demonstrated how phase-2 EADs and tissue-scale dynamical instabilities interact to result in PVCs and arrhythmias under LQTS, linking mechanistically phase-2 EADs to arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the disease phenotype of LQT2 and the onset of characteristic TdP arrhythmia or VT-like arrhythmia have been reported to be due to sudden arousal, exercise, sudden emotional or acoustic triggers or at rest during sleep, and are preceded by a pause in R-R interval with a transient dramatic rise in the QT interval immediately before the TdP [7,11,48]. T-wave alternans, T-wave liability (beat-to-beat variation) or oscillation in the ECG have been reported to be a precursor to lethal arrhythmia and major cardiac events in humans and in rabbit LQT2 models [49,50]. On clinical examination our symptomatic patient developed non-sustained ventricular tachycardia on a 24 h Holter recording while on beta-blocker bisoprolol and was implanted with an implantable cardioverter-defibrillator (ICD).…”
Section: What Is Causing Arrhythmogenic Events In Lqt2?mentioning
confidence: 99%
“…Therefore, T peakend -the length from the beginning of the T wave (T p ) to the end (T e ) on ECG-that reflect the transmural dispersion of repolarization was suggested to use as an indicator of arrhythmic risk, although, no clear consensus about the value of this parameter has been reached so far (Antzelevitch, 2008;Barbhaiya et al, 2013;Meijborg et al, 2014). Of note, dispersion of repolarization was recently identified (experimentally and by computational modeling) as cause for triggered activity/EAD formation, further enhancing the need to assess dynamic dispersion of repolarization noninvasively (Liu et al, 2018).…”
Section: Proarrhythmia Ecg Markers For Temporal Instability Of Repolamentioning
confidence: 99%